Conspiracy Theory Beliefs and Political Trust: The Moderating Role of Political Communication - Bernd Schlipphak; Mujtaba Isani; Mitja D. Back (Politics and Governance, 2022)
A plentitude of research has analyzed citizens’ belief in conspiracy theories and its individual‐level correlates. Yet, the effects of (political) context factors on the causes and effects of individual belief in conspiracy theories are still neglected. However, such context should be especially relevant when it comes to the impact of one’s belief in conspiracy theories on one’s political preference. In this article, we argue that the communication of governmental actors exerts a moderating influence on the link leading from a belief in conspiracy theories to political attitudes. In a nutshell, the belief in conspiracy theories should make citizens less likely to distrust their government—and the political system in general—in contexts where these theories are shared or at least publicly represented by governmental actors. Using two original data sets with data from Germany, Poland, and Jordan (Study 1) and data from Germany, Poland, Sweden, and France (Study 2), we test our argument based on an overall sample of about 10,000 cases. Our results indicate that higher degrees of generic conspiracy theories beliefs are associated with higher levels of political distrust across countries. Yet, confirming our argument, such an effect takes place less strongly in those countries in which governmental actors use conspiracy theories as a political communication strategy.